2015
DOI: 10.1007/s10450-015-9677-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of CuCl@AC with high CO adsorption capacity and selectivity from CO/N2 binary mixture

Abstract: The objective of this work is to develop CuCl@AC adsorbent with high CO capacity and selectivity from CO/N 2 binary gas mixture. A series of CuCl@AC adsorbents were prepared by a solid-state auto dispersion method, and then characterized by N 2 adsorption test, XRD and XPS. CO and N 2 adsorption isotherms on the adsorbents were measured by a volumetric method. The adsorption isotherms and selectivities of CuCl@AC adsorbents for CO/N 2 binary mixture were estimated on the basis of ideal adsorbed solution theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…These modified activated carbons show greater promise than the aforementioned commercially-available activated carbons for CO purification due to the incorporation of metal sites. First and second-row transition metals as well as post-transition metals salts such as Sn and Al have been LQFRUSRUDWHG LQWR DFWLYDWHG FDUERQV WKURXJK YDULRXV µPHWDO LPSUHJQDWLRQ ¶ PHWKRGV [53][54][55][56][57][58][59][60][61][62] Of the various metals, Cu impregnation is the most prominent. [53][54][55][56][57][58][59][60][61] Overall, as expected, the incorporation of transition metals such as copper increases the materials CO affinity and enhances the potential for selective CO separation, as exemplified in a study with CO/CO2/N2 mixtures.…”
Section: Activated Carbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…These modified activated carbons show greater promise than the aforementioned commercially-available activated carbons for CO purification due to the incorporation of metal sites. First and second-row transition metals as well as post-transition metals salts such as Sn and Al have been LQFRUSRUDWHG LQWR DFWLYDWHG FDUERQV WKURXJK YDULRXV µPHWDO LPSUHJQDWLRQ ¶ PHWKRGV [53][54][55][56][57][58][59][60][61][62] Of the various metals, Cu impregnation is the most prominent. [53][54][55][56][57][58][59][60][61] Overall, as expected, the incorporation of transition metals such as copper increases the materials CO affinity and enhances the potential for selective CO separation, as exemplified in a study with CO/CO2/N2 mixtures.…”
Section: Activated Carbonsmentioning
confidence: 99%
“…While using unsaturated metal sites to selectively adsorb CO molecules has been the most popular route for CO separation using MOFs to date, a number of studies have also been reported for which the goal was to introduce additional preferential adsorption sites through metal impregnation 84,116 and/or ligand functionalization ( Figure 2B). 115,124,125 Metal impregnation, similar to that reported with activated carbon, 59,60 has been performed on highly porous MOFs, e.g. MIL-100 and MIL-101.…”
Section: Co Adsorption Through Chemical Modification Of the Mofmentioning
confidence: 99%
“…To further improve MOFs' CO uptake, one can use metal impregnation, a method tested on ACs and zeolites. [9][10][11][12][13][14][15][16][17][18] This approach increases selectivity by decreasing the uptake of the undesired light product (e.g. N 2 ) whose affinity with the impregnated metal is low.…”
Section: Introductionmentioning
confidence: 99%
“…9 Several groups have produced Cu +impregnated zeolites and activated carbons either through the use of a Cu + -containing salt or that of a Cu 2+ -containing salt with subsequent reduction. [9][10][11][12][13][14][15][16][17][18] A similar route has also been conducted on Na-zeolite Y, initially through metal cation exchange with Cu 2+ ions. 19,20 These studies demonstrate that it is favourable to initially perform Cu 2+ impregnation or ionexchange, before reducing to Cu + .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation